ДОСЛІДЖЕННЯ ДВОНАПРЯМЛЕНОГО ПЕРЕТВОРЮВАЧА ПОСТІЙНОЇ НАПРУГИ УНІФІКОВАНОГО ІНВЕРТОРНОГО МОДУЛЯ ДЛЯ ЗАСТОСУВАННЯ В СИСТЕМАХ НАКОПИЧЕННЯ ЕНЕРГІЇ - Жаркін, А.Ф.; Пазєєв, А.Г.; Новський, В.О. (Інститут електродинаміки НАН України, Київ, 2018)
The results of the simulation modeling of a bidirectional dc-dc converter, which is part of the unified inverter module of multimodal systems of accumulation of electric power utilization, are presented, and the influence of the basic parameters and operating modes of the converter on the value of the currents of the power elements is investigated. The maximum values of currents and voltages in a 300 kW power converter are obtained, which provides the possibility of a reasonable choice of power switching elements, engineering calculations and the choice of power reactive elements and control system parameters.  Preferences 7, figures 5.